OVERVIEW OF ELDERLY BALANCE AT MEDICAL REHABILITATION, ULIN HOSPITAL, BANJARMASIN - Fauziah, Enny (Politeknik Unggulan Kalimantan, 2024)
Elderly would decreased in body physiology, especially those that affect balance control, such as decreased muscle strength, changes in posture, fat levels that accumulate in certain areas, decreased proprioception and visual impairment. This results in poor balance control for the elderly, which can increase the risk of falls in the elderly. The method used is a descriptive survey. Meanwhile, for the qualitative (random) research design, the target of the activity was aimed at the adult and elderly community at the Medical Rehabilitation of Ulin Hospital, Banjarmasin, as many as 34 people. Meanwhile, there were 11 active respondents for balance checks. Based on the results of the research that had been carried out, it was found that the average age of middle age was 52.4 years with a total of 7 people and the elderly was 63.75 years with a total of 4 people. Meanwhile, in the results of the single leg stance, it was found that the risk level for falls was in the single leg stance open eyes with an average age of 58.9 years, a total of 9 people with an average standing time of 26.3 seconds. In the single leg stance closed eyes, the level of risk of a risky fall was obtained with an average age of 57.7 years, a total of 10 people with a standing time on one leg of 2.9 seconds. Conclusion: Respondents experienced balance disorders with a risk level of risky falls based on the single leg stance open eyes test with the number 9 people with an average age of 58.9 years closed eyes with 10 respondents with an average age of 57.7 years. Keywords: Balance, Single Leg Stance Test, Elderly